An investigation into the use of the ParaDNA® body fluid identification system in forensic examinations. (December 2017) - Doole, Sharon
Abstract: Examinations carried out in forensic laboratories currently utilise chemical screening tests and microscopic analysis to locate and identify body fluids. However, there are currently no reliable tests to positively identify vaginal material, to differentiate between venous and menstrual blood and to confirm the presence of azoospermic semen. Furthermore, for cases involving allegations of oral intercourse, the attribution of a positive amylase reaction to saliva (as opposed to vaginal secretions) can be problematic. LGC has developed a system that uses the ParaDNA system together with one-tube mRNA detection chemistry for body fluid identification. This can be utilized at the laboratory examination stage, prior to DNA testing, to positively identify body fluids. A series of mRNA markers were selected to positively identify saliva, vaginal secretions, peripheral blood, menstrual blood, seminal fluid and sperm cells. We have carried out an assessment of this system in an active casework environment using mock-case samples. To investigate the sensitivity and specificity of the mRNA markers, the system was tested both by direct sampling of the body fluid stain (using the ParaDNA sampling device), and using aliquots of the retained aqueous supernatant following cell-harvesting. This paper summarises the findings obtained from the initial experiments carried out, together with the results of a further investigation into the effect of mixed body fluid samples on the detection of the individual body fluids.